2021
DOI: 10.1128/msphere.00114-21
|View full text |Cite
|
Sign up to set email alerts
|

Defining Polysaccharide-Specific Antibody Targets against Vibrio cholerae O139 in Humans following O139 Cholera and following Vaccination with a Commercial Bivalent Oral Cholera Vaccine, and Evaluation of Conjugate Vaccines Targeting O139

Abstract: Cholera is a severe dehydrating illness of humans caused by Vibrio cholerae serogroup O1 or O139. Protection against cholera is serogroup specific, and serogroup specificity is defined by O-specific polysaccharide (OSP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Antigens were produced as previously described [33][34][35][36][37][38], or purchased from a commercial source, and are described in detail in the testing protocol. OSP antigens were produced as OSP:BSA (bovine serum albumin) conjugates to facilitate binding to the polysterene beads [33][34][35]. All antigens were conjugated to Luminex magnetic beads using carbodiimide coupling according to the manufacturer's recommendations.…”
Section: Serological Testing and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigens were produced as previously described [33][34][35][36][37][38], or purchased from a commercial source, and are described in detail in the testing protocol. OSP antigens were produced as OSP:BSA (bovine serum albumin) conjugates to facilitate binding to the polysterene beads [33][34][35]. All antigens were conjugated to Luminex magnetic beads using carbodiimide coupling according to the manufacturer's recommendations.…”
Section: Serological Testing and Data Processingmentioning
confidence: 99%
“…Additionally, O139 serogroup OSP (V. cholerae O139 serogroup is rarely detected as circulating in the last decade, but is included in the most commonly used oral cholera vaccines), heat labile enterotoxin subunit B (LT-B), and heat labile holo-enterotoxin (LT-H) (expressed during infection with enterotoxigenic Escherichia coli [ETEC] and have a high degree of homology with cholera toxin counterparts) and influenza haemaglutinin 1 (Flu) (as a control antigen) were also selected. Antigens were produced as previously described [33][34][35][36][37][38], or purchased from a commercial source, and are described in detail in the testing protocol. OSP antigens were produced as OSP:BSA (bovine serum albumin) conjugates to facilitate binding to the polysterene beads [33][34][35].…”
Section: Serological Testing and Data Processingmentioning
confidence: 99%
“…Additionally, O139 serogroup OSP ( V. cholerae O139 serogroup has been rarely detected as circulating in the last decade, but is included in the most commonly used oral cholera vaccines), heat-labile enterotoxin subunit B (LT-B), and heat-labile holo-enterotoxin (LT-H) (expressed during infection with enterotoxigenic Escherichia coli [ETEC] and have a high degree of homology with cholera toxin counterparts) and influenza hemaglutinin 1 (flu) (as a control antigen) were also selected. Antigens were produced as previously described ( 29 , 30 , 40 43 ), or purchased from a commercial source, and are described in detail in the testing protocol. OSP antigens were produced as OSP:BSA (bovine serum albumin) conjugates to facilitate binding to the polystyrene beads ( 40 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…Antigens were produced as previously described ( 29 , 30 , 40 43 ), or purchased from a commercial source, and are described in detail in the testing protocol. OSP antigens were produced as OSP:BSA (bovine serum albumin) conjugates to facilitate binding to the polystyrene beads ( 40 42 ). All antigens were conjugated to Luminex magnetic beads using carbodiimide coupling according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, V. cholerae O139 expresses a capsule comprised of a polymer of the OSP-hexasaccharide ( 15 , 18 21 ), while V. cholerae O1 is unencapsulated. We have previously characterized the immune response to O139 OSP and its fragments using pooled human patient serum samples and found that the terminal tetrasaccharide of the OSP-hexasaccharide is particularly immunogenic ( 22 ). Despite the importance of OSP-specific responses in mediating protection against cholera caused by V. cholerae O1 ( 23 ), little is known about OSP-specific responses in individual patients infected with V. cholerae O139 and in vaccine recipients of bivalent (O1/O139) oral killed cholera vaccine (OCV) currently included in the global stockpile of cholera vaccine and used in cholera control programs.…”
Section: Introductionmentioning
confidence: 99%